PENGARUH TERAPI KOMPRES HANGAT TERHADAP INTENSITAS NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III di TPMB WIWIN WULANDARI CIKARANG UTARA - Siregar, Rohani; Widiasari, Wiwin; Sholihat, Kikie (Jurnal Delima Harapan, 2025)
Background: Pregnant women often experience lower back pain, especially in the lumbosacral area, due to changes in posture, weight gain, and spinal structure. Objective: To determine the effect of warm compresses on lower back pain, a common complaint among pregnant women in the third trimester. Method: This study used a pre-experimental one-group pretest-posttest design, where subjects were measured at baseline (pretest), received an intervention, and were measured again (posttest). The study involved 30 respondents selected using the Shapiro-Wilk technique. The research instrument included applying warm compresses using a towel and measuring lower back pain using the Numeric Rating Scale (NRS) and Visual Analog Scale (VAS). Data analysis was performed using the Wilcoxon test. Results: warm compress therapy significantly reduced the intensity of lower back pain (p = 0.00; P < 0.05). Conclusion: Warm compresses are recommended as a simple and effective way to reduce lower back pain in pregnant women during the third trimester without using medication.